PENINGKATAN KUALITAS PELAYANAN PUBLIK DI PEMERINTAH DAERAH KABUPATEN BATANG MELALUI SISTEM PENGELOLAAN PENGADUAN PELAYANAN PUBLIK NASIONAL (SP4N)-LAPOR - Kusroh Lailiyah (RISTEK : Jurnal Riset, Inovasi dan Teknologi Kabupaten Batang, 2023)
Abstract This study aims to find out the implementation of the SP4N-LAPOR application in the Regional Government of Batang Regency and its influence on improving the quality of public services in Batang Regency. This study uses a qualitative approach through descriptive analysis method based on the study of the literature obtained and then used as material for analysis. The results of this study indicate that if you use the LAPOR! Bupati, which has been integrated with the SP4N-LAPOR application in Batang Regency, has been implemented quite well. This can be seen by the user satisfaction rate for this application which reached 75.7 percent in 2020. The LAPOR! Bupati This regent was launched to accelerate the follow-up to the settlement of public service complaints. The complaint process is also very easy because the public or users can report remotely via various SMS channels 1708, the Batangkab.go.id portal, mobile apps and the #LAPOR l708 tweeter. Complaint settlement is also relatively fast, namely a maximum of 7 working days. With the presence of the LAPOR! Bupati, the Batang Regency government can create increasingly excellent public services with the ease of public service complaints that can be accessed by all levels of society. Keywords: SP4N-LAPOR, Public Service Complaints, LAPOR! Bupati of Batang Regency